(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Industrial automation systems are used to control and monitor a process, machine or device in a computerized manner that usually fulfils repetitive functions or tasks. The application of PLCs is increasing day by day in automation industry. Filling is the task that is carried out by a machine and this process is widely used in many industries. The objective of this paper is to design, develop and monitor different size bottle filling and capping system using PLC LogixPro simulation. To develop the process of bottle filling of different sizes and capping using animated simulation as a study material for PLC based automation system. PLC ladder diagram approach is used for the study. In this study, the bottles lines up for filling automatically. The system checks for broken bottles and open the gate to divert the broken bottles into scrap area where it is collected in a box. The remaining bottles moves continuously on the main conveyor belt. Sensors are added to measure the height of the bottles and to turn on the filling station accordingly. This will avoid overfilling or less filling of the bottles. The filled bottles continue to move on the conveyor belt until the capping station. The sensor at the capping station identifies the presence of the bottles and initiated the capping system. Once capped, the weight sensor attached at the bottom of the main conveyor belt identifies the large size bottles and opens the gate to divert the large size bottles to large size bottle conveyor to make it easier for packaging. The remaining small size bottles in the main conveyor are packaged separately. The operation of the PLC program is tested at each step and results are presented. The results shows that the program is implemented successfully. The developed automated system can be used a case study to teach the PLC basics since all the major components counters, sensors, Indicator lights, switches, are incorporated.